Non-tubal Ectopic Pregnancy - Elito, Julio Jr (IntechOpen, 2020)
"Non-Tubal Ectopic Pregnancy" is a comprehensive book, written in an organized and concise format. The book offers an immersion into non-tubal ectopic pregnancy and the reader is invited, chapter after chapter, to visit the most important aspects of non-tubal ectopic pregnancies. The book covers all aspects of non-tubal ectopic pregnancies including epidemiology, diagnosis, and management. Experts from all over the world have contributed to it, bringing the best from their research.The book presents the reader with the latest advances on non-tubal ectopic pregnancies.